Evaluasi Hasil Pembelajaran Sains Melalui Implementasi Studi Independen dan Model Pembelajaran Berbasis Riset (PBR) - Syazali, Muhammad; Widiada, I Ketut; Rahmatih, Aisa Nikmah; Husniati, Husniati; Hayati, Ilmi Solihana; Elvira, Baiq Olivia Dwita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Evaluation of learning outcomes is an important component in the educational process. Primarily in implementing relatively new learning facilities. The aim of this research is to evaluate student science learning outcomes. The sample consisted of 86 students who were facilitated with independent study and the PBR model. Learning outcome data is collected using the documentation method from the final assessment results sheet which becomes the grade on the student's study results card. This data was analyzed descriptively to determine the average size and proportion. To find out the comparison of science learning outcomes between semester 3 and semester 5 students, an inferential analysis was carried out using the independent sample t-test. Our findings show that the average student science learning outcomes are in the good category. As many as 94.2% of students received a pass grade in the science courses they programmed. The results of the inferential analysis that we carried out show that the science learning achievements of semester 3 and semester 5 students are significantly different. Semester 5 has higher science learning outcomes compared to semester 3 students. The results of this research prove that the implementation of independent study and the PBR model is effective in helping students to master the assigned science learning objectives well, and the semester level has a significant effect. However, the quality of the learning process needs to be improved because there is a small percentage (5.8%) whose mastery of science learning objectives cannot be categorized as passing. It is hoped that this improvement can improve their science learning outcomes, so that in the next lesson, they can reach the pass category with a good or very good interpretation.